Influence of physical and material parameters on switching current density in perpendicular STT-MTJ: a micromagnetic study - Abhishree Shaw; Vinod Kumar Joshi (Journal of Physics Communications)
Switching in magnetic tunnel junctions (MTJs) is considered to be coherent according to the macrospin model but above a critical characteristic length (R _c ) this process becomes incoherent. As a result, switching becomes a complex process and affects the switching current density (J _c ). We designed a spin transfer torque (STT) based single barrier perpendicular MTJ (SMTJ) and observed the influence of the junction size and exchange stiffness constant (A _ex ) on the switching process through micromagnetic simulations performed on Object Oriented Micromagnetic Framework (OOMMF). It was found that coherent switching occurred only for junction diameter ≤20nm and showed dependence on A _ex as well. The influence of damping constant and anisotropy on J _c is studied and the mechanism of magnetic reversal through domain formation is revisited in this work. Furthermore, Double barrier MTJ (DBMTJ) stack was designed, which showed increased STT efficiency in switching time with a requirement of J _c lower by 42.86% compared to SMTJ.